Dipolo e escoamento uniforme: escoamento em torno de um cilindro circular - Santos, Eduardo José dos [UNESP] (2011)
The study of movements of ideals fluids is more simple that the viscous fluids because do not have the presence of tension of shear. The normal tensions are the one that must be considered in this analysis. The theory corresponding to these flows is the same used in other fields of the physics called Theory of Potentials Fields, which the vector identity is fundamental. Any flow into irrotational (null vorticity) physically possibly has a current function and a potential of velocity that satisfied the equation of Laplace. Reciprocally, any solution of equation of Laplace represents a current function or a potential of velocity of a flow into physically possible. Once the equation of Laplace is linear, the addiction of any numbers of solutions is also a solution. So, several potentials flows into can be constructed superposing configurations of elementary flows into. The purpose of the superposition of elementary flows into is a production of similar configurations to those of practical interest. The combination of mathematical elegancy with utility in the potential flow into attracted many for its study. Some of the most famous mathematician of history studied the theory and application of “hydrodynamic”, how was called the potential fluid into before 1900